Effect of bone quality and quantity on the primary stability of dental implants in a simulated bicortical placement - Rues, Stefan; Schmitter, Marc; Kappel, Stefanie; Sonntag, Robert; Kretzer, Jan Philippe; Nadorf, Jan (Clinical oral investigations, 2021)
Conventional dental implants inserted in the molar region of the maxilla will reach into the sinus maxillaris when alveolar ridge height is limited. When surgery is performed without prior augmentation of the sinus floor, primary stability of the implant is important for successful osseointegration. This study aimed at identifying the impact of bone quality and quantity at the implantation site on primary implant stability of a simulated bicortical placement.
Published online: 10 July 2020
Gesehen am 04.10.2021